IL6 Gene Polymorphism and Oral Cancer: A Review - Mehwish Zafar; Naila Hadi; Saeeda Baig (ziauddin University, 2024)
Abstract: Oral cancer is labeled as one of the most common human malignancy worldwide. Regardless of the advancements made in its treatment it has a very low 5 years survival rate. This is due to late diagnoses and poor responses to treatment because of advanced/late stage at the time of presentation. Specific early biomarkers are required that can predict severity and stage of the disease. Inflammatory cytokines especially, IL-6 plays a central role in cancer. IL-6, a pro-inflammatory cytokine, secreted by various cells of the body, has been thoroughly investigated in oral cancer development and progression by various studies. An electronic article search was done through PubMed, Google Scholar and Medscape, using the following keywords: oral cancer, Interleukin-6 and IL6 gene polymorphism. All types of articles were included to discuss the role of IL 6 gene polymorphism in the development of oral cance r. Key Words: IL 6 Gene Polymorphism, Oral cancer.